A transposable element insertion in the susceptibility gene CsaMLO8 results in hypocotyl resistance to powdery mildew in cucumber. Issue 1 (December 2015) - Berg, Jeroen; Appiano, Michela; Santillán Martínez, Miguel; Hermans, Freddy; Vriezen, Wim; Visser, Richard; Bai, Yuling; Schouten, Henk
Abstract Background Powdery mildew (PM) is an important disease of cucumber (Cucumis sativus L.).CsaMLO8 was previously identified as a candidate susceptibility gene for PM in cucumber, for two reasons: 1) This gene clusters phylogenetically in clade V, which has previously been shown to harbour all knownMLO -like susceptibility genes for PM identified in dicot species; 2) This gene co-localizes with a QTL on chromosome 5 for hypocotyl-specific resistance to PM. Methods CsaMLO8 alleles from susceptible and resistant cucumber were cloned and transformed tomlo -mutant tomato. Cucumber seedlings were inoculated withPodosphaera xanthii, tissues were studied for CsaMLO8 expression at several timepoints post inoculation using qRT-PCR. The occurence of the observed loss-of-function allele ofCsaMLO8 in resequenced cucumber accessions was studiedin silico . Results We clonedCsaMLO8 alleles from susceptible and resistant cucumber genotypes, the latter carrying the QTL for hypocotyl resistance. We found that insertion of a non-autonomous Class LTR retrotransposable element in the resistant genotype leads to aberrant splicing ofCsaMLO8 mRNA. Heterologous expression of the wild-type allele ofCsaMLO8 in a tomatomlo- mutant restored PM susceptibility. However, heterologous expression of theCsaMLO8 allele cloned from the resistant cucumber genotype failed to restore PM susceptibility. Furthermore we showed that inoculation of susceptible cucumber with the PM pathogenPodosphaera xanthii induced transcriptional upregulation ofCsaMLO8 in hypocotyl tissue, but not in cotyledon or leaf tissue. This coincides with the observation that the QTL at theCsaMLO8- locus causes full resistance in hypocotyl tissue, but only partial resistance in cotyledons and true leafs. We studied the occurrence of the loss-of-function allele ofCsaMLO8 in cucumber germplasm by anin silico approach using resequencing data of a collection of 115 cucumber accessions, and found that this allele was present in 31 out of 115 accessions. Conclusions CsaMLO8 was characterised as a functional susceptibility gene to PM, particularly in the hypocotyl where it was transcriptionally upregulated upon inoculation with the PM pathogenP. xanthii. A loss-of-function mutation inCsaMLO8 due to the insertion of a transposable element was found to be the cause of hypocotyl resistance to PM. This particular allele ofCsaMLO8 was found to occur in 27 % of the resequenced cucumber accessions.